EXPLORING THE RISKS AND BENEFITS OF USING ARTIFICIAL INTELLIGENCE IN CORPORATE FORESIGHT - Ebrahimabadi, Samaneh (My University, 2024)
Given the central role that scientific innovation and technological advancements play in driving social changes and economic developments, it is essential to understand how to leverage the benefits of innovations effectively within the context of corporate foresight. The rapid advancements in artificial intelligence (AI) technologies have generated substantial interest in exploring how these innovations can enhance various domains of human activity. In this regard, it is imperative for corporate foresight to capitalize on the potential benefits offered by AI while also carefully navigating the associated risks and challenges. Through the use of 10 semi-structured interviews thematised with qualitative content analysis, this thesis explores the multifaceted implications resulting from using artificial intelligence in corporate foresight. The results of this thesis reveal several key benefits associated with using AI in corporate fore-sight. Specifically, the findings indicate that AI can facilitate enhanced data integration, improve the accuracy of analyses, increase productivity, enhance data visualization, and contribute to time savings. However, the study also highlights various limitations and challenges surrounding the adoption of AI in this context, including integration and adoption barriers, algorithmic limitations, resource constraints, and data dependencies. Furthermore, the research identifies potential risks when integrating AI into corporate fore-sight practices. These risks include the magnification of human cognitive biases, demographic biases, over-reliance on AI outputs, social risks, security risks, and ethical concerns. The ex-pert interviews also suggest that the future of AI in corporate foresight may involve a spectrum of outcomes, ranging from AI serving as a human assistant to potentially replacing hu-man decision-makers. The results of this study indicate that the use of AI in corporate foresight projects can have both short-term and long-term impacts. The theoretical implications of this research suggest that human intervention remains crucial, not only for practical necessity but also for establishing trust in AI, ensuring its healthy evolution, and delivering more reliable solutions to real-world problems.

با توجه به نقش محوری که نوآوری علمی و پیشرفت‌های فناوری در ایجاد تغییرات اجتماعی و توسعه اقتصادی ایفا می‌کنند و کارکرد حیاتی آینده‌نگاری در تدوین برنامه‌ها و استراتژی‌های آینده‌نگر، ضروری است که بدانیم چگونه می‌توان به طور موثر از مزایای نوآوری در چارچوب آینده نگاری شرکتی استفاده کرد. پیشرفت‌های سریع در فناوری‌های هوش مصنوعی (AI) علاقه قابل توجهی به کشف این که چگونه این نوآوری‌ها می‌توانند حوزه‌های مختلف فعالیت انسانی را بهره‌مند سازند، ایجاد کرده است. در این راستا، برای آینده‌نگاری شرکتی ضروری است که روی مزایای بالقوه ارائه‌شده توسط هوش مصنوعی سرمایه‌گذاری کند و در عین حال خطرات و چالش‌های مرتبط را نیز با دقت بررسی کند. این پایان نامه از طریق استفاده از ۱۰ مصاحبه نیمه ساختاریافته با روش تحلیل محتوای کیفی (تحلیل مضمون)، پیامدهای چندوجهی ناشی از استفاده از هوش مصنوعی در آینده نگاری شرکتی را بررسی می‌کند. نتایج این پایان نامه چندین مزیت کلیدی مرتبط با استفاده از هوش مصنوعی در آینده نگاری شرکتی را نشان می‌دهد. به طور خاص، یافته‌ها نشان می‌دهد که هوش مصنوعی می‌تواند یکپارچه‌سازی داده‌ها را تسهیل کند، دقت تجزیه و تحلیل‌ها را بهبود بخشد، بهره‌وری را افزایش دهد، تجسم داده‌ها را افزایش دهد و به صرفه‌جویی در زمان کمک کند. با این حال، این مطالعه همچنین محدودیت‌ها و چالش‌های مختلف پیرامون به کارگیری هوش مصنوعی در این زمینه، از جمله موانع یکپارچه‌سازی و پذیرش، محدودیت‌های الگوریتمی، محدودیت‌های منابع و وابستگی‌های داده را برجسته می‌کند. این تحقیق، همچنین خطرات بالقوه را هنگام ادغام هوش مصنوعی در شیوه های آینده نگاری شرکتی شناسایی می‌کند. این خطرات شامل بزرگ‌نمایی سوگیری‌های شناختی انسان، سوگیری‌های جمعیتی، اتکای بیش از حد به خروجی‌های هوش مصنوعی، ریسک‌های اجتماعی، خطرات امنیتی و نگرانی‌های اخلاقی است. مصاحبه‌های کارشناسان همچنین نشان می‌دهند که آینده هوش مصنوعی در آینده‌نگاری شرکتی ممکن است شامل طیفی از نتایج باشد، از عملکرد هوش مصنوعی به عنوان دستیار انسانی تا جایگزینی بالقوه تصمیم‌گیرندگان انسانی. نتایج این مطالعه نشان می‌دهد که استفاده از هوش مصنوعی در پروژه‌های آینده‌نگاری شرکتی می‌تواند تأثیرات کوتاه‌مدت و بلندمدت داشته باشد. یافته‌های نظری این تحقیق نشان می‌دهد که مداخله انسانی نه تنها برای ضرورت عملی، بلکه برای ایجاد اعتماد به هوش مصنوعی، تضمین تکامل سالم آن، و ارائه راه‌حل‌های قابل اعتمادتر برای مشکلات دنیای واقعی، حیاتی است.
Keywords: Corporate foresight, Artificial intelligence, Foresight